Cardinal Adam Easton (c. 1330-1397) : monk, scholar, theologian, diplomat - Wendling, Miriam (Church, faith, and culture in the Medieval West., 2020)
The varied career of Adam Easton (c. 1330-1397) led him from Norwich Cathedral Priory to Oxford, Avignon and Rome. Not only a monk of the Benedictine Order, he was also a scholar, theologian, diplomat and cardinal, and his work reflects the breadth of this multifaceted background. This volume presents recent research on Easton's oeuvre, his diplomacy, and the books that accompanied him on his travels. Amongst the works addressed in this volume are Easton's Defensorium ecclesiastice potestatis, his Defensorium S. Birgittae and his Office for the Feast of the Visitation. Further new evidence is also offered on his testimony during the Great Schism, on the dating of his copy of De pauperie Salvatoris, while two reassessments are made of his likeness, including his sepulchral monument at S. Cecilia in Rome and the Lutterwork wall painting. Finally, a catalogue of Easton's important manuscript collection is also provided.